Lepanthes cordillerana (Orchidaceae) a new species and the landscape threats to its wild populations - Parra-Sánchez, Edicson; Restrepo, Eugenio; Alegría-Valencia, Melisa; Moreno, Juan Sebastián; Galindo-Tarazona, Robinson (Phytotaxa, 2023)
Extensive fieldwork carried out on the Andean forests of Colombia resulted in the discovery of Lepanthes cordillerana, described here as a novel taxon. The new species is most similar to Lepanthes teres from Ecuador, from which it can be easily distinguished by the ciliated margins of the leaf, the oblong-acute lower lobe of the petals and the capitate, cuneate basally, apically caved, villose appendix. Despite its wide distribution across the three Colombian mountain ranges, a landscape analysis shows that 50% of the recorded wild populations of the endemic Lepanthes cordillerana are under threat of habitat loss and landscape fragmentation. Conservation efforts should be directed to reduce landscape scale threats to their populations.